2003
DOI: 10.1046/j.1365-2826.2003.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin‐Releasing Factor Type‐1 Receptor mRNA is Not Induced in Mouse Hypothalamus By Either Stress or Osmotic Stimulation

Abstract: In rats, acute stress substantially increases corticotropin-releasing factor (CRF) type 1 receptor (CRFR-1) mRNA expression in the paraventricular nucleus (PVN) and osmotic stimulation induces both CRF and CRFR-1 mRNA in magnocellular PVN and supraoptic nucleus (SON). However, these phenomena have not been analysed in other species. We compared CRF and CRFR-1 expression in rat and mouse hypothalamus. Male C57BL/6 mice and Wistar rats were exposed to acute restraint stress for 3 h, or to hypertonic saline inges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Previously, using CRH deficient (CRH KO) and wild type (WT) mice, we reported that WT mice showed an increase in CRH mRNA in the hypothalamus following a 2-h restraint stress, but failed to show an elevation in hypothalamic CRH-R1 mRNA (Makino et al, 2005), consistent with results from others (Imaki et al, 2003). In rats, it has been demonstrated that both CRH and CRH-R1 mRNA in the hypothalamus are up-regulated by various types of stressors (Makino et al, 1995).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previously, using CRH deficient (CRH KO) and wild type (WT) mice, we reported that WT mice showed an increase in CRH mRNA in the hypothalamus following a 2-h restraint stress, but failed to show an elevation in hypothalamic CRH-R1 mRNA (Makino et al, 2005), consistent with results from others (Imaki et al, 2003). In rats, it has been demonstrated that both CRH and CRH-R1 mRNA in the hypothalamus are up-regulated by various types of stressors (Makino et al, 1995).…”
Section: Discussionsupporting
confidence: 88%
“…In rats, it has been demonstrated that both CRH and CRH-R1 mRNA in the hypothalamus are up-regulated by various types of stressors (Makino et al, 1995). Central administration of CRH increased CRH-R1 mRNA in the hypothalamus, and the effect of CRH was blocked by alpha-helical CRH (Imaki et al, 2003). Direct infusion of CRH into the dorsal PVN was also shown to induce CRH-R1 mRNA in CRH-positive neurons in the parvocellular part of the PVN (Imaki et al, 2003), suggesting that CRH increases the amplitude of its own response to stress by increasing the number of CRH-R1 receptors in the hypothalamus of rats (Ono et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity for antibodies against CRF‐R1, 5‐HT or c‐Fos has been described elsewhere (Imaki et al. , 2003; Hayashi et al.…”
Section: Methodsmentioning
confidence: 99%
“…Mice consume alcohol [9, 34, 50], and show increased consumption in response to footshock stress in a strain-dependent manner [31, 32]. Interestingly, there is evidence that rats and mice differ in behavioral and neural responses to stressors [1, 2, 5, 21, 48] and in the neuroanatomical organization of brain areas implicated in stress [1, 2, 5, 21, 48]. We will therefore contrast the effects of the pharmacological stressors yohimbine and FG-7142 on the expression of c-fos and CRF mRNA in the brains of C57 BL/6J mice.…”
Section: Introductionmentioning
confidence: 99%